E- COMMERCE DISTRO TODAY: E-commerce;MySQl;Structured System Analysis and Design. - Suana, Irma; Widya Sari, Syantika (LP2M Universitas Nurdin Hamzah, 2022)
E-commerce is an online sales system by utilizing internet technology. E-commerce provides convenience for customers who want to make purchases and make it easier for stores to sell products in order to expand their marketing reach. Distro Today is a store engaged in the sale of men's and women's clothing and serves shoe,bags, and wearpack washing services. The sales system in Distro Today still uses a manual system, soithas limited marketing areas and buyers. To solve the problem, Distro Today E-commerce was created that can handle online sales. Distro Today e-commerce was developed with structured system analysis and desaign (SSAD) model, PHP programming language and MySQL database management system.E- commerce as a promotional medium, providing product information, ordering transaction services for customers, and automatic recording of sales transactions so as to help improve the sales and expanding the Distro Today market.